Counter-narratives for the prevention of violent radicalisation: a systematic review of targeted interventions - Carthy, Sarah L. (Campbell Systematic Reviews, 2020)
The objective of this review was to provide a synthesis of the effectiveness of counter-narratives in reducing the risk of violent radicalisation.